De uil in de grot. Gesprekken met beelden, kunstenaars en schrijvers. - Baert, Barbara; Vervenne, Marc; de Zegher, Catherine; De Bruyckere, Berlinde; Pattyn, Chantal; Wittockx, Eva; Debruyne, Heleen; Van Kerckhoven, Anne-Marie; Vandenbroeck, Paul; Vanderveken, Thomas; De Wachter, Dirk; Eyskens, Mark (Kalmthout : Pelckmans Pro.)
Kiefer, Anselm ; Bouts, Dirk ; Emin, Tracey ; Bernini, Giovanni ; Dujourie, Lili ; Braeckman, Dirk ; de Goya, Francisco ; Beuys, Joseph ; Guston, Philip ; Van de Velde, rinus ; De Keersmaeker, Anne Teressa ; Bosch, Jheronimus
boek